COMPARISON OF TRIGGER POINT INJECTION APPLICATION METHODS IN MYOFASCIAL PAIN SYNDROME IN PATIENTS WITH FIBROMYALGIA SYNDROME - Elbasti, M. S.; Yentur, S. Baglan (Elsevier, 2024)
[Abstract Not Available]
Meeting of the European-Alliance-of-Associations-for-Rheumatology (EULAR) -- JUN 12-15, 2024 -- Vienna, AUSTRIA
Keywords: Physical therapy/Physiotherapy; Pain; Rehabilitation